A composite material for repairing cadmium pollution in farmland, a preparation method and application thereof
Patent Information
- Application Number
- CN202510468347.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-15
- Publication Date
- 2026-09-08
- Estimated Expiration
- 2045-04-15
AI Technical Summary
[0010]针对以上问题,本发明提供一种用于修复农田镉污染的复合材料及制备方法与应用,该复合材料通过铁铝基钝化材料与生物炭的优化结合及功能化改性,解决了传统钝化材料在制备工艺、吸附效率和环境安全性中的技术瓶颈,显著提升了镉污染修复效果
[0027] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention provides a systematic method for preparing composite materials. Through the pretreatment, mixing, segmented pyrolysis and surface functionalization modification of iron-aluminum based passivation materials and biochar, a composite material for efficiently remediating cadmium pollution in farmland is prepared, which solves the problems of immature preparation process, low adsorption efficiency and insufficient environmental safety of traditional passivation materials, and significantly improves the remediation effect of cadmium pollution.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of heavy metal contaminated farmland remediation technology, specifically a composite material for remediating cadmium pollution in farmland, its preparation method, and its application. Background Technology
[0002] Soil, as a fundamental resource for human survival and development, directly impacts food security, ecological stability, and public health. Studies indicate that cadmium, mercury, and lead are major pollutants in farmland soils. The persistent and accumulative nature of heavy metals poses long-term risks to ecosystems and human health, necessitating efficient remediation technologies.
[0003] Currently, soil passivation technology has become the mainstream choice for the remediation of heavy metal pollution in farmland due to its ease of operation and short remediation cycle. Passivation materials are mainly divided into the following two categories: 1. Organic passivation materials: surface materials such as biochar, humic acid, and animal manure compost. Their advantages are improving soil structure (e.g., increasing organic matter content and promoting aggregate formation), enhancing water retention and aeration, and reducing the bioavailability of cadmium by complexing heavy metals through functional groups (carboxyl and hydroxyl groups). For example, biochar can fix cadmium ions due to its porous structure and abundant surface active sites; humic acid indirectly reduces cadmium absorption by supplementing nutrients and promoting plant growth. However, there are also limitations: the adsorption capacity of a single organic material is limited, and its long-term stability is insufficient, making it susceptible to microbial degradation. 2. Inorganic passivation materials: lime-based materials (adjust pH, reduce cadmium solubility); phosphate-based materials (form stable mineral precipitates); silicate-based materials (high specific surface area adsorption); iron-manganese oxides (redox and complexation); industrial waste (such as iron-aluminum based passivation materials, fly ash, utilizing alkalinity and mineral components to passivate heavy metals). Their advantages include high passivation efficiency, making them suitable for moderately to heavily polluted soils. Limitations: They can easily alter soil physicochemical properties (e.g., excessively increasing pH disrupts microbial balance), and some materials (such as iron-aluminum based passivation materials) contain impurities of heavy metals, posing a risk of secondary pollution.
[0004] Iron-aluminum based passivation materials (aluminum industry waste slag) are rich in iron, aluminum oxides, and alkaline components, which can effectively fix cadmium and regulate soil pH; biochar has a high specific surface area and functionalized surface. Combining the two holds promise for overcoming the limitations of single-material applications. Existing research has explored iron-aluminum based passivation material-biochar composites (RM / BC), for example, the co-pyrolysis of RM and biomass can reduce ferric oxide in RM to Fe. 0 A novel Fe-modified BC composite material (RM / BC) was synthesized, showing good performance in removing pollutants. However, the following key issues remain in current research:
[0005] 1. Immature preparation process: The physical properties of iron-aluminum based passivation materials and biochar differ greatly, and uneven mixing leads to performance fluctuations; the mineral phase transformation during pyrolysis is uncontrollable, affecting the stability of the material.
[0006] 2. The pore structure and surface functional groups (such as carboxyl and hydroxyl groups) of biochar are key to the adsorption of heavy metals, but the alkalinity of iron-aluminum based passivation materials may destroy the acidic functional groups of biochar and reduce the adsorption efficiency.
[0007] 3. Environmental risks are unclear: Iron-aluminum based passivation materials contain trace amounts of heavy metals (such as Cd content of 0.14 mg / kg), and long-term application may lead to cumulative risks; the long-term stability of composite materials in dynamic soil environments lacks verification.
[0008] 4. In actual contaminated soil, there are often multiple heavy metals such as cadmium, lead, and arsenic. The adsorption sites of the composite material may be occupied by other ions, resulting in a decrease in the selective adsorption capacity for cadmium.
[0009] In summary, developing a highly efficient, stable, and environmentally friendly iron-aluminum based passivation material and biochar composite material, and optimizing its preparation process, is a key direction for breaking through current technological bottlenecks and realizing large-scale remediation of cadmium pollution in farmland. Summary of the Invention
[0010] To address the above problems, this invention provides a composite material for remediating cadmium pollution in farmland, its preparation method, and its application. This composite material, through the optimized combination and functional modification of iron-aluminum based passivating materials and biochar, solves the technical bottlenecks of traditional passivating materials in terms of preparation process, adsorption efficiency, and environmental safety, and significantly improves the remediation effect of cadmium pollution.
[0011] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0012] A method for preparing a composite material for remediating cadmium pollution in farmland, comprising the following specific steps:
[0013] Step 1, Pretreatment of iron-aluminum based passivation material: Mix iron-aluminum based passivation material with hydrochloric acid solution at a liquid-solid ratio of 3-5:1, mechanically stir for 12-24 hours, filter, wash with water until neutral, dry, and ball mill to a particle size ≤50μm;
[0014] Step 2, Biochar pretreatment: Rice straw is pyrolyzed and ground to obtain biochar, which is then immersed in hydrogen peroxide solution and ultrasonically treated at 50-60℃ for 1.5-2.5h. After filtration, it is dried and passed through a 100-mesh sieve.
[0015] Step 3, Mixing: The iron-aluminum based passivation material pretreated in Step 1 and the biochar pretreated in Step 2 are mixed at a mass ratio of 1:2-4, and then fed into a twin-screw extruder for gradient extrusion. The extrudate is granulated and cooled to room temperature to obtain mixed granules.
[0016] Step 4, staged pyrolysis: Place the mixed particles in a tube furnace. In the first stage, heat the mixture to 400-450℃ and hold it under a nitrogen atmosphere for 1-1.5 hours. In the second stage, switch to a carbon dioxide atmosphere and heat the mixture to 700-750℃ at the same rate. Hold it for 1-1.5 hours and then cool it to below 50℃ before removing it.
[0017] Step 5, surface functionalization modification: The mixed particles after pyrolysis are immersed in sodium sulfide solution and shaken at 25-30℃ for 2-2.5h. After filtration and drying, the silane coupling agent is uniformly sprayed onto the material surface using fluidized bed spraying equipment and cured at 60-80℃ for 30-60min to obtain the composite material.
[0018] In a preferred embodiment, the concentration of hydrochloric acid solution in step 1 is 1.5-2.5 mol / L, and the mechanical stirring speed is 200-300 rpm. This technical solution determines the optimal concentration of hydrochloric acid solution and mechanical stirring speed in the pretreatment of iron-aluminum based passivation materials, ensuring that impurities in the iron-aluminum based passivation materials can be fully removed, while avoiding over-acidification or uneven stirring, thereby improving the purity of the iron-aluminum based passivation materials and the uniformity of subsequent reactions.
[0019] In a preferred embodiment, the washing process in step 1 involves a neutral pH of 6.5-7.5, a ball milling speed of 300-400 rpm, and a time of 2-4 hours. This technical solution clarifies the pH range for washing the iron-aluminum based passivation material to neutral pH and the optimal ball milling speed and time, ensuring the neutralization treatment and particle size refinement of the iron-aluminum based passivation material, thereby improving its surface activity and compatibility with other materials.
[0020] In a preferred embodiment, the hydrogen peroxide concentration in step 2 is 2-4%, and the liquid-to-solid ratio is 4-5:1. This technical solution determines the optimal hydrogen peroxide concentration and liquid-to-solid ratio in the pretreatment of biochar. Ultrasonic treatment can effectively oxidize the surface of biochar, increase the number of surface functional groups, and thus improve the adsorption capacity of biochar for cadmium ions.
[0021] In a preferred embodiment, the twin-screw extruder in step 3 is set to a speed of 45-55 rpm, with the following barrel temperature gradients: zone 1 80-90℃, zone 2 100-110℃, and zone 3 120-130℃. This technical solution optimizes the speed of the twin-screw extruder and the barrel temperature gradient, ensuring uniform mixing of the iron-aluminum based passivation material and biochar to form stable composite particles, providing a good foundation for the subsequent pyrolysis reaction.
[0022] In a preferred embodiment, the heating rate in step 4 is 8-10℃ / min, the nitrogen flow rate is 150-200mL / min, and the carbon dioxide flow rate is 200-250mL / min. This technical solution determines the heating rate and gas flow rate in the staged pyrolysis process, ensuring the stable progress of the pyrolysis reaction and allowing the iron-aluminum based passivation material and biochar to react fully under different atmospheres, forming a composite material with excellent adsorption properties.
[0023] In a preferred embodiment, in step 5, the concentration of sodium sulfide solution is 0.1-0.15 mol / L, the silane coupling agent is KH550, and the solvent is ethanol with a concentration of 1-2%.
[0024] In a preferred embodiment, the spraying pressure in step 5 is 0.2-0.3 MPa, and the atomized particle size is 20-30 μm.
[0025] Under optimal conditions, the specific surface area of the composite material is 180-220 m². 2 / g, micropore ratio ≥60%, surface sulfur group density ≥0.5mmol / g.
[0026] Under optimal conditions, the composite material is used for the remediation of cadmium pollution in rice paddies. The application method is as follows: spread the composite material evenly on the soil surface, till to a depth of 20-25cm, let it stand for 7-10 days, and then sow it. It is also used in combination with hyperaccumulating plants such as Sedum aizoon or Spatholobus suberectus, with a planting density of 2000-3000 plants / mu.
[0027] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention provides a systematic method for preparing composite materials. Through the pretreatment, mixing, segmented pyrolysis and surface functionalization modification of iron-aluminum based passivation materials and biochar, a composite material for efficiently remediating cadmium pollution in farmland is prepared, which solves the problems of immature preparation process, low adsorption efficiency and insufficient environmental safety of traditional passivation materials, and significantly improves the remediation effect of cadmium pollution.
[0028] (2) This invention removes residual alkaline oxides (sodium oxide, calcium oxide) and soluble impurities (such as chloride ions) from iron-aluminum based passivation materials through pretreatment, increases iron oxide content, enhances the active sites of iron oxides in iron-aluminum based passivation materials, and increases the specific surface area of iron-aluminum based passivation materials through ball milling, promoting uniform mixing and pyrolysis reaction contact with biochar in the subsequent process; hydrogen peroxide is used to pretreat biochar, oxidize the surface of biochar, increase the density of carboxyl and hydroxyl functional groups, enhance the complexation ability of cadmium, and ultrasonic treatment enhances hydrogen peroxide penetration through cavitation effect, uniformly modifying the pore structure of biochar.
[0029] (3) This invention uses twin-screw gradient extrusion to achieve molecular-level mixing of iron-aluminum based passivation material and biochar through shear force and thermal melting, avoiding local aggregation and improving material uniformity. Temperature gradient control (zone one to zone three) softens the biochar, and the iron-aluminum based passivation material particles are embedded in its porous structure to form a stable "mineral-carbon" composite skeleton. Then, staged pyrolysis is used. In the first stage, the biochar carbon skeleton is stabilized to avoid excessive oxidation and retain the microporous structure. In the second stage, carbon dioxide reacts with iron oxide in the iron-aluminum based passivation material to generate magnetic iron(II,III) oxide, which enhances the magnetic separation and recovery capability of the material. At the same time, carbon dioxide activates the surface of biochar, etches biochar to form more micropores, and increases the specific surface area.
[0030] (4) This invention modifies the mixed particles with sulfur groups to introduce sulfur groups. The sulfur groups form stable thiols complexes with cadmium ions. Cadmium ions are selectively adsorbed through soft acid-soft base interaction, reducing interference from competing ions such as lead ions and arsenic ions. A hydrophobic protective layer is formed by coating with silane coupling agent. After hydrolysis, the silane coupling agent condenses with hydroxyl groups on the material surface to form a Si-O-Si network structure, which coats the active sites of heavy metals, reduces the leaching risk of residual cadmium in iron-aluminum based passivation materials, and enhances the stability of materials in moist soil. Detailed Implementation
[0031] To enable those skilled in the art to better understand the technical solution, the present invention will be described in detail below with reference to embodiments. The description in this part is only exemplary and explanatory, and should not be used to limit the scope of protection of the present invention in any way.
[0032] The iron-aluminum based passivation materials used in the following examples and comparative examples were produced by a Chinese aluminum company using the Bayer-sintering combined method. After being naturally air-dried, they were passed through a 200-mesh sieve. The pH value of the iron-aluminum based passivation materials was 11.28, and the organic matter content was 6.09 mg / kg.
[0033] Example 1:
[0034] A method for preparing a composite material for remediating cadmium pollution in farmland, comprising the following specific steps:
[0035] Step 1, Pretreatment of iron-aluminum based passivation material: The iron-aluminum based passivation material is mixed with hydrochloric acid solution at a liquid-solid ratio of 3:1 and mechanically stirred for 20 hours. After filtration, it is washed with water until neutral, dried, and then ball-milled until the particle size is ≤50μm. The concentration of the hydrochloric acid solution is 1.5mol / L, the mechanical stirring speed is 300rpm, the pH value of washing until neutral is 7.5, the ball milling speed is 300rpm, and the time is 3 hours.
[0036] Step 2, Biochar pretreatment: Rice straw is pyrolyzed and ground to obtain biochar, which is then immersed in hydrogen peroxide solution and ultrasonically treated at 60°C for 1.5 hours. After filtration, it is dried and passed through a 100-mesh sieve. The hydrogen peroxide solution has a mass concentration of 2% and a liquid-to-solid ratio of 5:1.
[0037] Step 3, Mixing: The iron-aluminum based passivation material pretreated in Step 1 and the biochar pretreated in Step 2 are mixed at a mass ratio of 1:4, and then fed into a twin-screw extruder for gradient extrusion. The extrudate is granulated and cooled to room temperature to obtain mixed granules. The twin-screw extruder is set with a rotation speed of 45 rpm and a barrel temperature gradient of 90°C in Zone 1, 100°C in Zone 2, and 130°C in Zone 3.
[0038] Step 4, Segmented pyrolysis: The mixed particles are placed in a tube furnace. In the first stage, the temperature is raised to 400°C and held at that temperature for 1.5 hours under a nitrogen atmosphere. In the second stage, the temperature is switched to a carbon dioxide atmosphere and raised to 700°C at the same rate. The temperature is held for 1.5 hours and then cooled to below 50°C before being removed. The heating rate is 8°C / min, the nitrogen flow rate is 200 mL / min, and the carbon dioxide flow rate is 200 mL / min.
[0039] Step 5, Surface functionalization modification: The mixed particles after pyrolysis are immersed in sodium sulfide solution, shaken at 25°C for 2.5 hours, filtered and dried, and then a silane coupling agent is uniformly sprayed onto the material surface using a fluidized bed spraying device. The composite material is obtained by curing at 60°C for 60 minutes. The concentration of the sodium sulfide solution is 0.1 mol / L, the silane coupling agent is KH550, the solvent is ethanol with a concentration of 1%, the spraying pressure is 0.3 MPa, and the atomized particle size is 20-25 μm.
[0040] Example 2:
[0041] A method for preparing a composite material for remediating cadmium pollution in farmland, comprising the following specific steps:
[0042] Step 1, Pretreatment of iron-aluminum based passivation material: The iron-aluminum based passivation material is mixed with hydrochloric acid solution at a liquid-solid ratio of 4:1, mechanically stirred for 15 hours, filtered, washed with water until neutral, dried, and ball-milled until the particle size is ≤50μm. The concentration of the hydrochloric acid solution is 2.5mol / L, the mechanical stirring speed is 200rpm, the pH value of washing until neutral is 6.5, the ball milling speed is 400rpm, and the time is 2 hours.
[0043] Step 2, Biochar pretreatment: Rice straw is pyrolyzed and ground to obtain biochar, which is then immersed in hydrogen peroxide solution and ultrasonically treated at 50°C for 2.5 hours. After filtration, it is dried and passed through a 100-mesh sieve. The hydrogen peroxide solution has a mass concentration of 4% and a liquid-to-solid ratio of 4:1.
[0044] Step 3, Mixing: The iron-aluminum based passivation material pretreated in Step 1 and the biochar pretreated in Step 2 are mixed at a mass ratio of 1:3, and then fed into a twin-screw extruder for gradient extrusion. The extrudate is granulated and cooled to room temperature to obtain mixed granules. The twin-screw extruder is set with a rotation speed of 55 rpm and a barrel temperature gradient of 80°C in Zone 1, 110°C in Zone 2, and 120°C in Zone 3.
[0045] Step 4, Segmented pyrolysis: The mixed particles are placed in a tube furnace. In the first stage, the temperature is raised to 450°C and held at that temperature for 1 hour under a nitrogen atmosphere. In the second stage, the temperature is switched to a carbon dioxide atmosphere and raised to 750°C at the same rate. The temperature is held for 1 hour and then cooled to below 50°C before being removed. The heating rate is 10°C / min, the nitrogen flow rate is 150 mL / min, and the carbon dioxide flow rate is 250 mL / min.
[0046] Step 5, Surface functionalization modification: The mixed particles after pyrolysis are immersed in sodium sulfide solution, shaken at 30°C for 2 hours, filtered and dried, and then a silane coupling agent is uniformly sprayed onto the material surface using a fluidized bed spraying device. The composite material is obtained by curing at 70°C for 45 minutes. The concentration of sodium sulfide solution is 0.15 mol / L, the silane coupling agent is KH550, the solvent is ethanol with a concentration of 2%, the spraying pressure is 0.2 MPa, and the atomized particle size is 23-30 μm.
[0047] Example 3:
[0048] A method for preparing a composite material for remediating cadmium pollution in farmland, comprising the following specific steps:
[0049] Step 1, Pretreatment of iron-aluminum based passivation material: The iron-aluminum based passivation material is mixed with hydrochloric acid solution at a liquid-solid ratio of 5:1 and mechanically stirred for 24 hours. After filtration, it is washed with water until neutral, dried, and then ball-milled until the particle size is ≤50μm. The concentration of the hydrochloric acid solution is 2.0mol / L, the mechanical stirring speed is 250rpm, the pH value of washing until neutral is 7.3, the ball milling speed is 380rpm, and the time is 4 hours.
[0050] Step 2, Biochar pretreatment: Rice straw is pyrolyzed and ground to obtain biochar, which is then immersed in hydrogen peroxide solution and ultrasonically treated at 55°C for 2.2 hours. After filtration, it is dried and passed through a 100-mesh sieve. The hydrogen peroxide solution has a mass concentration of 3% and a liquid-to-solid ratio of 5:1.
[0051] Step 3, Mixing: The iron-aluminum based passivation material pretreated in Step 1 and the biochar pretreated in Step 2 are mixed at a mass ratio of 1:2, and then fed into a twin-screw extruder for gradient extrusion. The extrudate is granulated and cooled to room temperature to obtain mixed granules. The twin-screw extruder is set with a rotation speed of 50 rpm and a barrel temperature gradient of 85°C in Zone 1, 108°C in Zone 2, and 125°C in Zone 3.
[0052] Step 4, Segmented pyrolysis: The mixed particles are placed in a tube furnace. In the first stage, the temperature is raised to 420°C and held at that temperature for 1.3 hours under a nitrogen atmosphere. In the second stage, the temperature is switched to a carbon dioxide atmosphere and raised to 730°C at the same rate. The temperature is held for 1.1 hours and then cooled to below 50°C before being removed. The heating rate is 9°C / min, the nitrogen flow rate is 180 mL / min, and the carbon dioxide flow rate is 220 mL / min.
[0053] Step 5, Surface functionalization modification: The mixed particles after pyrolysis are immersed in sodium sulfide solution, shaken at 28°C for 2.3 hours, filtered and dried, and then a silane coupling agent is uniformly sprayed onto the material surface using a fluidized bed spraying device. The composite material is obtained by curing at 80°C for 30 minutes. The concentration of the sodium sulfide solution is 0.12 mol / L, the silane coupling agent is KH550, the solvent is ethanol with a concentration of 1.5%, the spraying pressure is 0.3 MPa, and the atomized particle size is 20-28 μm.
[0054] Comparative Example 1:
[0055] A method for preparing a composite material for remediating cadmium pollution in farmland, comprising the following specific steps:
[0056] Biochar and iron-aluminum based passivation material were mixed at a mass ratio of 3:1 and placed in a ceramic container. The material was heated in a tube furnace at a rate of 10℃ / min, and N2 gas was injected into the chamber. Heating continued until the temperature reached 700℃, and the pyrolysis holding time was set to 2h. The iron-aluminum based passivation material and biochar composite material were obtained.
[0057] Comparative Example 2:
[0058] The difference between this comparative example and Example 1 is that step 1, the pretreatment step of the iron-aluminum based passivation material, is omitted, and the raw material iron-aluminum based passivation material is directly mixed with biochar, while the other steps remain unchanged.
[0059] Comparative Example 3:
[0060] The difference between this comparative example and Example 1 is that step 2, the biochar pretreatment step, is omitted, and the untreated biochar and the iron-aluminum based passivation material are directly mixed, while the remaining steps remain unchanged.
[0061] Comparative Example 4:
[0062] The difference between this comparative example and Example 1 is that in step 5, the mixed particles are dried after filtration to directly obtain the composite material product, omitting the spraying step.
[0063] Comparative Example 5:
[0064] The difference between this comparative example and Example 1 is that in step 5, the mixed particles are directly sprayed and cured to obtain the finished product, omitting the sodium sulfide chemical treatment step.
[0065] To verify the technical effectiveness of this invention, a series of experiments were conducted.
[0066] 1. Soil cultivation experiment
[0067] Analytical grade CdCl2 was used as the cadmium source and added to the test soil in solution to achieve a high cadmium concentration. The soil was thoroughly mixed to a moisture content of approximately 40%, and reacted at room temperature (25℃±2℃) for 14 days. Afterward, the mixture was air-dried in a ventilated area and ground for later use. 10g of the composite materials prepared in Examples 1-3 and Comparative Examples 1-5 were evenly sprinkled into 1000g of soil samples. The treated soil was placed in a well-ventilated location, and to prevent dust interference, a layer of plastic wrap was gently covered on the soil surface. This condition was maintained, allowing the soil to stand in a ventilated environment for 7 days. After 7 days, a portion of the soil sample was taken, using a quartering method to ensure representativeness. The taken samples were then air-dried in a natural environment. Once completely dry, the soil was broken up for subsequent preservation and testing. The passivation effect of the samples was then tested. By analyzing the cadmium ion concentration in the soil, the cadmium ion immobilization capacity of the composite material was evaluated. Simultaneously, the pH value of the soil samples was measured to understand the impact of the composite material on soil acidity and alkalinity. The test results are shown in the table below.
[0068] Table 1
[0069]
[0070]
[0071] 2. Toxicity leaching test
[0072] The leachates of the composite materials from Examples 1-3 and Comparative Example 4 were analyzed in detail according to the national environmental protection standard HJ 557-2010, "Leaching Toxicity of Solid Waste - Horizontal Oscillation Method". The results are shown in Table 2. The potential environmental risks of the iron-aluminum based passivation material and biochar composite material were analyzed and assessed by referring to the relevant standard limits in the "Integrated Wastewater Discharge Standard" and the "Farmland Irrigation Water Quality Standard".
[0073] Table 2
[0074]
[0075] 3. Specific surface area analysis experiment of composite materials
[0076] Using the standard degassing station of the Micromeritics instrument, the samples were pretreated for 8 hours under vacuum at 150°C. Then, using a Micromeritics APSP 2460 4-station fully automated specific surface area analyzer, nitrogen adsorption-desorption tests were performed on the composite material samples obtained in Examples 1-3 and Comparative Examples 1-5 under liquid nitrogen conditions at 77K. After the instrument analysis was completed, isothermal adsorption-desorption curves were obtained, and the total specific surface area of the material was obtained by the BET method. The results are shown in the table below.
[0077] Table 3
[0078]
[0079]
[0080] It should be noted that, in this document, the terms "comprising," "including," and any other variations are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Specific examples have been used in this document to illustrate the principles and implementation methods of the present invention. These examples are merely for the purpose of helping to understand the method and core ideas of the present invention. The above descriptions are only preferred embodiments of the present invention. It should be pointed out that, due to the limitations of written expression and the objective existence of infinite specific structures, those skilled in the art can make several improvements, modifications, or variations without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner. These improvements, modifications, variations, or combinations, or the direct application of the concept and technical solution of the present invention to other situations without modification, should all be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a composite material for remediating cadmium pollution in farmland, characterized in that, The specific steps are as follows: Step 1, Pretreatment of iron-aluminum based passivation material: Mix iron-aluminum based passivation material with hydrochloric acid solution at a liquid-solid ratio of 3-5:1, mechanically stir for 12-24 hours, filter, wash with water until neutral, dry, and ball mill to a particle size ≤50μm; Step 2, Biochar pretreatment: Rice straw is pyrolyzed and ground to obtain biochar, which is then immersed in hydrogen peroxide solution and ultrasonically treated at 50-60℃ for 1.5-2.5h. After filtration, it is dried and passed through a 100-mesh sieve. Step 3, Mixing: The iron-aluminum based passivation material pretreated in Step 1 and the biochar pretreated in Step 2 are mixed at a mass ratio of 1:2-4, and then fed into a twin-screw extruder for gradient extrusion. The extrudate is pelletized and cooled to room temperature to obtain mixed granules. The twin-screw extruder is set with a rotation speed of 45-55 rpm and a barrel temperature gradient of: Zone 1 80-90℃, Zone 2 100-110℃, and Zone 3 120-130℃. Step 4, Segmented pyrolysis: The mixed particles are placed in a tube furnace. In the first stage, the temperature is raised to 400-450℃ and held under a nitrogen atmosphere for 1-1.5 hours. In the second stage, the temperature is switched to a carbon dioxide atmosphere and raised to 700-750℃ at the same rate, held for 1-1.5 hours, and then cooled to below 50℃ before being removed. The heating rate is 8-10℃ / min, the nitrogen flow rate is 150-200mL / min, and the carbon dioxide flow rate is 200-250mL / min. Step 5, surface functionalization modification: The mixed particles after pyrolysis are immersed in sodium sulfide solution and shaken at 25-30℃ for 2-2.5h. After filtration and drying, the silane coupling agent is uniformly sprayed onto the material surface using a fluidized bed spraying device and cured at 60-80℃ for 30-60min to obtain the composite material. The concentration of the sodium sulfide solution is 0.1-0.15mol / L, the silane coupling agent is KH550, and the solvent is ethanol with a concentration of 1-2%.
2. The method for preparing a composite material for remediating cadmium pollution in farmland according to claim 1, characterized in that, In step 1, the concentration of hydrochloric acid solution is 1.5-2.5 mol / L, and the mechanical stirring speed is 200-300 rpm.
3. The method for preparing a composite material for remediating cadmium pollution in farmland according to claim 1, characterized in that, In step 1, the washing process is carried out until the pH value is neutral (6.5-7.5), the ball milling speed is 300-400 rpm, and the time is 2-4 hours.
4. The method for preparing a composite material for remediating cadmium pollution in farmland according to claim 1, characterized in that, In step 2, the hydrogen peroxide concentration is 2-4% and the liquid-to-solid ratio is 4-5:
1.
5. A method for preparing a composite material for remediating cadmium pollution in farmland according to claim 1, characterized in that, In step 5, the spraying pressure is 0.2-0.3 MPa and the atomized particle size is 20-30 μm.
6. The composite material prepared by the method according to any one of claims 1-5, characterized in that, The composite material has a specific surface area of 180-220 m² / g, a micropore ratio of ≥60%, and a surface sulfur group density of ≥0.5 mmol / g.
7. The application of the composite material according to claim 6, characterized in that, The composite material is used for the remediation of cadmium pollution in rice paddies. The application method is as follows: spread the composite material evenly on the soil surface, till to a depth of 20-25cm, let it stand for 7-10 days, and then sow it. It can be used in combination with hyperaccumulating plants such as Sedum aizoon or Spatholobus suberectus, with a planting density of 2000-3000 plants / mu.
Citation Information
Patent Citations
Iron-manganese modified biochar for remediation and treatment of cadmium-polluted soil as well as preparation method and application method of iron-manganese modified biochar
CN115637150A
Sodium polysulfide-based soil mercury pollution stable repairing agent based on solar self-loading and preparation method of sodium polysulfide-based soil mercury pollution stable repairing agent
CN117106452A